Providing public intradomain traffic matrices to the research community. - Uhlig, Steve
This paper presents a new publicly available dataset from GÉANT, the European Research and Educational Network. This dataset consists of traffic matrices built using full IGP routing information, sampled Netflow data and BGP routing information of the GÉANT network, one per 15 minutes interval for several months. Potential benefits of publicly available traffic matrices comprise improving our understanding of real traffic matrices, their dynamics, and to make possible the benchmarking of intradomain traffic engineering methods
Keywords: Computer systems organization; Computer communication networks; Network operations; Network monitoring; Local and wide area networks; Internet (e.g., TCP/IP).